Animal Models of Interferon Signature Positive Lupus - Zhuang, Haoyang; Szeto, Christopher; Han, Shuhong; Yang, Lijun; Reeves, Westley H. (Frontiers in Immunology, 2015)
Human lupus is strongly associated with a gene expression signature characterized by over-expression of type I interferon-regulated genes. A strong interferon signature is not seen in the standard mouse models of lupus, despite considerable evidence for the involvement of toll-like receptor (TLR)-driven interferon production. In contrast, pristane-induced lupus exhibits a prominent TLR7-dependent interferon signature. Importantly, genetic disorders with dysregulated interferon production in both humans and mice cause severe autoinflammatory diseases but not the typical manifestations of lupus suggesting that interferon over-production by itself is insufficient to cause SLE. Murine single-gene models suggest that lupus-like disease may result from abnormalities in B cell activation and the clearance of dead cells. Pristane may mimic human SLE by causing interferon production along with synergistic abnormalities affecting clearance of apoptotic cells and activation of B cell signaling.